The Validity and Reliability Grade Primary School EFL Students’ Final Speaking Test - Anis Zayyana (Indonesian Postgraduate Foreign Language Education Association, 2025)
The study underscores the essential importance of mastering English speaking skills at an early age as mandated by Indonesia’s Merdeka curriculum, which establishes English speaking as a vital subject for assessment in primary education. To ensure the effectiveness of the speaking test used for sixth-grade EFL students, the study focuses on evaluating the validity and reliability of the test. Using a qualitative methodology that combines interviews with an English teacher serving as the rater and document analysis, the research investigates multiple facets of test quality. The findings demonstrate that the speaking test is valid through the application of content validity—confirming the relevance and representativeness of test items—and consequential validity, which considers the implications and fairness of the test outcomes. Moreover, reliability is verified via intra-rater reliability, indicating that the scoring is consistent when conducted by the same evaluator over time. Ultimately, the study concludes that the speaking test for sixth-grade primary school EFL students possesses excellent quality in both validity and reliability. Consequently, it suggests that other educational institutions with similar levels and objectives may confidently adopt or adapt the test’s design, scoring rubric, and rating procedures to improve their own assessment practices